Overexpression of Mutant FKRP Restores Functional Glycosylation and Improves Dystrophic Phenotype in FKRP Mutant Mice - Jason D. Tucker; Pei J. Lu; Xiao Xiao; Qi L. Lu (Elsevier, 2018)
Autosomal recessive homozygous or compound heterozygous mutations in FKRP result in forms of muscular dystrophy-dystroglycanopathy varying in age of onset, clinical presentation, and disease progression, ranging from the severe Walker-Warburg, type A,5 (MDDGA5), muscle-eye-brain (MDDGB5) with or without cognitive deficit, to limb-girdle type 2I (MDDGC5). Phenotypic variation indicates degrees of functionality of individual FKRP mutation, which has been supported by the presence of residual expression of functionally glycosylated α-dystroglycan (DG) in muscles of both animal models and patients. However, direct evidence showing enhancement in glycosylation of α-DG by mutant FKRP is lacking. Using AAV9-mediated overexpression of mutant human FKRP bearing the P448L mutation (mhFKRP-P448L) associated with severe congenital muscular dystrophy (CMD), we demonstrate the restoration of functional glycosylation of α-DG and reduction in markers of disease progression. Expression of mhFKRP-P448L also corrects dystrophic phenotypes in the models of L276I mutation with mild disease phenotype and causes no obvious histological or biomarker alteration in C57BL/6 normal mice. Our results confirm the existing function of mutant FKRP. The results also suggest that mutant FKRP could be an alternative approach for potential gene therapy should normal FKRP gene products be immunogenic.